The Relationship Between Clinical Nurse Career Path and The Implementation of Public Service Interaction Behavior at Dr. Rehatta Hospital, Central Java Province - Buchori Setyoaji Prayodya; Indanah; Sri Siska Mardiana; Andy Sofyan Prasetyo (CV. Inara, 2026)
The quality of nursing services in hospitals is a crucial factor that affects public satisfaction and trust. Issues related to service complaints in Jepara underline the importance of nurse professionalism, one of which is developed through a career level system. This study aims to analyze the relationship between the career path of clinical nurses and the implementation of public service interaction behavior at dr. Rehatta Hospital, Central Java Province. This quantitative research uses a correlation design with a cross-sectional approach. The study population was 106 clinical nurses, with a sample of 84 nurses selected through stratified random sampling techniques. Data was collected using a questionnaire referring to Permenkes No. 33 of 2019, then analyzed univariately to describe the characteristics of respondents and bivariate with the Spearman Rank Correlation Test. The results of the study showed that the majority of respondents had public service interaction behavior in the